STUDIES ON ANTIBACTERIAL ACTIVITY OF SEAWEEDS, ENTEROMORPHA INTESTINALIS (LINNAEUS) AND GELIDIELLA ACEROSA (FORSSKAL) FROM PUDUCHERRY AND RAMESWARAM (SOUTHEAST COAST OF INDIA) - NOBEL SURYA PANDIDURAI R; KALAVATHI K; PERUMAL P (International Journal of Pharma and Bio Sciences, 2014)
The main objective of the work was to evaluate and compare the invitro antibacterial activity of seaweed using different solvent system. Seaweeds, Enteromorpha intestinalis and Gelidiella acerosa, collected from Puducherry and Rameshwaram (South East Coast of India). From the dried seaweeds extracts of crude bioactive compounds were obtained using the solvents of acetone, diethyl ether, methanol:chloroform (1:1). The seaweed extracts were tested against 12 human bacterial pathogens by disc diffusion method. The methanol:chloroform extracts showed maximum zone of inhibition against Bacillus subtilis, Streptococcus pneumonia, Vibrio cholera and Proteus mirabilis. The HPTLC analysis of E.intestinalis methanol:chloroform extracts showed 14 different phytochemical compounds. From the present study, it can be concluded that the green alga Enteromorpha intestinalis is a potential source of bioactive compounds.